Does the enterprise’s choice of intangible capital help to promote its ESG score? - Gao, Jie; Li, Jiahao; Luo, Yuwei (Frontiers in Environmental Science, 2022)
Digital transformation, as an important way to optimize the existing resources of enterprises, is a driving force to achieve their high-quality development. Intangible capital is used to reflect the status of digital transformation of enterprises, so as to explore the relationship between the decision of enterprises on digital transformation and the ESG scoring effect of enterprises under financing constraints. The results show that when enterprises are faced with strong financing constraints, the management's decision on digital transformation tends to be conventional. Although maintaining the traditional business model is more beneficial, it is not conducive to the improvement of ESG score. To further analyze the digital transformation mechanism of enterprises, this paper examines the decision-making behavior of enterprises under financing constraints from the perspective of intermediary mechanism. The results show that the decision of increasing intangible capital of enterprises promotes the improvement of enterprise performance, and then drives the promotion of the enterprise ESG score. This study enriches the research achievements in the field of digital transformation of enterprises, and provides reference for heterogeneous enterprises to select digital transformation decisions.